Commodity Windfalls, Polarization, and Net Foreign Assets : Panel Data Evidenceon the Voracity Effect - Bruckner, Markus; Arezki, Rabah (Washington, D.C. : International Monetary Fund, 2010)
This paper examines the effect that windfalls from international commodity price booms have on net foreign assets in a panel of 145 countries during the period 1970-2007. The main finding is that windfalls from international commodity price booms lead to a significant increase in net foreign assets, but only in countries that are homogeneous. In polarized countries, net foreign assets significantly decreased. To explain this asymmetry, the paper shows that in polarized countries commodity windfalls lead to large increases in government spending, political corruption, and the risk of expropriation, with no overall effect on GDP per capita growth. The paper's findings are consistent with theoretical models of the current account that have a built-in voracity effect.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet